Seismic Behavior of Hybrid Coupled Wall System - Wihardja, Thavera; Imran, Iswandi (Institut Teknologi Sepuluh Nopember, 2017)
Reinforced concrete (RC) couple wall systems, where RC beams couple two or more RC walls in series, are frequently used in high-rise buildings. Generally, coupling beams are made of RC materials. Steel coupling beam is an alternative for RC coupling beam which has a complex and and unefficient detailing construction. This paper presents a study on the use of Hybrid Coupled Wall System (HCWS) in seismic resistant high-rise RC structures. In the study, 25 storey office buildings with three types of coupling beams and three types of walls distributed over the height of the structure and located in a region with high seismicity are designed. Applying a performance-based design approach, this study developed an efficient design for RC structures having Coupling Ratio (CR) values 64.55% and affect the behavior of the wall pier in the upper region of the structure where widespread plastification and earlier crushing failure happen. Based on this findings, steel coupling beams can be used as an alternative with statisfying all performance criteria and perform at Life Safety(LS).